Intergenerational Education: Theological Foundations and Implementation on Modern Christian Education in Indonesia - DARMAWAN, I Putu Ayub; WENAS, Maria Lidya; DIANA, Ruat (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
Intergenerational education plays an important role in modern Christian education, as it fosters a sense of community, encourages spiritual growth, and facilitates the transmission of faith across generations. It explores developmental psychology's perspective, emphasizing individuals' diverse needs at different stages of life. In addition, it highlights the significant impact of religious engagement, intergenerational closure, and extracurricular participation on educational outcomes. This article explores the theological foundations of intergenerational education in the context of modern Christian education. Drawing on numerous scholarly works, he examines the importance of reciprocal, place, and theological praxis approaches in intergenerational education. It also discusses the importance of understanding the developmental characteristics of children in the Christian faith. In addition, this article highlights the value of intergenerational ministry and the role of learning theory in supporting the intergenerational Christian experience. It concludes by emphasizing the importance of intergenerational Christian education in local churches and the potential benefits of intergenerational learning programs for participants and organizations.